Analisis Tokoh Sukat dalam Naskah Drama Lakon Yang Ditulis Kemudian Adaptasi dari Novel Hari Terakhir di Rumah Bordil Karya Bode Riswandi Menggunakan Pendekatan Psikologi Sastra dan Relevansinya dengan Pembelajaran Bahasa Indonesia (International Forum of Researchers and Lecturers, 2024)
The background of this research is to analyze the character of Sukat using analysis of Sigmund Freud's literary psychology theory, the aim is to find out the causes of the character Sukat experiencing disturbances in his personality, and also to find out the alleged disturbance that occurred to the character Sukat in the performance of the Play Written Later by Bode Riswandi. The method used is a qualitative method. The technique used in this study is data collection techniques. Data collection techniques used are reading techniques and note-taking techniques. From this analysis it is concluded that the character Sukat has a feeling of revenge from a dark past, the reason Sukat did the heinous thing to Dahlia was because of what happened at that time. Sukat's younger sister was sold by her father as a gambling bet and many of her gambling friends felt that her younger sister had committed suicide before leaving school. It was this feeling of revenge that made Sukat dark and his eyes darkened and he thought that every girl should feel what her sister had experienced.